PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA MATERI PERUBAHAN ENERGI KELAS IV SD NEGERI 76 PEKANBARU - Indra Mayudin; Laili Rahmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
One of the learning models based on constructivist theory is the Problem-Based Learning (PBL) model. In this model, the teacher is responsible for gradually guiding students through learning activities. The teacher is also responsible for applying the strategies and skills necessary to solve problems. This study aims to explore the impact of problem-based learning (PBL) on the achievement of science teaching processes, especially on the content about environmental changes, for fourth-grade students at SD Negeri 76 Pekanbaru. This approach is a quantitative approach with a type of research that is a Quasi-Experimental. The research design used is the One Group Pre-Test-Post-Test Design. Based on the research results and discussions outlined in the previous chapters, it can be concluded that the t calculated > t table at a significance level of 5% (12.519 > 1.694) and has a value of 0.000 < 0.05, which means it can be concluded that there is a significant increase in the science learning scores of students on the topic of energy changes in class IVA SDN 76 Pekanbaru. By applying PBL, students not only learn about the concept of energy changes in theory but also understand how to apply it in real-life situations, increasing their engagement and understanding, as well as preparing them for future challenges.